Study on the development of sustainability measurement for Malaysia rural public libraries / Siti Khadijah Rafie and Roziya Abu - Rafie, Siti Khadijah; Abu, Roziya (Universiti Teknologi MARA, Kedah, 2019)
Sustainability is a subject that often been widely discussed in many fields. In Malaysia, sustainability that have been highlighted in 11th Malaysia Plan, with the aim for a future that is built on the focus of macroeconomic policy including improving Malaysian wellbeing, human capital development that is future-proof, green and sustainable growth, and infrastructure that supports economic development and a citizen-centric public service with high productivity. Eventually, many Malaysian local and international sectors are now implementing sustainability in their organization, and it’s time for the library to follow this trend in order to keep the existence of libraries. This study focuses on sustainability of rural libraries in Malaysia which is handled by National Library of Malaysia (NLM). Discussion in this article focuses on the three crucial aspects of sustainable development, namely; economic, environmental and social with concentration on library staffing and the users and non-users of rural libraries all over Malaysia.